Epilepsy in children - Passi, Gouri; Tora, Sharad; Goswami, VP; Yewale, Vijay; Rawat, SS; Mulye, Swati (India : Jaypee Brothers Medical Publishers, 2014)
Children have the highest incidence of epilepsy compared to any other age category. However, 70% of newly diagnosed children with epilepsy can undergo remission if treated appropriately. Unfortunately in developing countries, more than three quarters of patients with epilepsy, do not receive adequate treatment. There have been dramatic changes in the landscape of pediatric epilepsy. The classification is always in a state of flux. Partial onset epilepsy is now to be called focal epilepsy. The term complex partial epilepsy has been discarded to be called dyscognitive seizures. In fact, the first identified channelopathy was a defect in the potassium channel in benign familial neonatal seizures. Genetic underpinnings of many other types of epilepsy are slowly being unraveled; such as generalized epilepsy with febrile seizures plus which is now known to be caused by a defect in voltage-gated sodium channels. Diagnostic tools such as high resolution magnetic resonance imaging (MRI) have revealed many different patterns of neuronal migration abnormalities, including periventricular nodular heterotopias, band heterotopias, small cortical dysplasia and perisylvian heterotopias. Positron emission tomography (PET) and single photon emission computed tomography (SPECT) scans, SISCOM, functional magnetic resonance imaging (fMRI) and magnetoencephalography are coming slowly into clinical use. While clinicians are still coming to terms with the indications and adverse effects of newer drugs such as topiramate, lamotrigine, zonisamide, lacosamide, levetiracetam and brivaracetam, new side effects such as blue skin discoloration with retigabine are being reported. Alternative therapy for refractory epilepsy such as the ketogenic diet and epilepsy surgery has also made small determined steps in India. Pediatricians need to keep abreast of current literature in pediatric epilepsy. This book is a small attempt in that direction. Pediatric neurologists from around the country have contributed to compile a comprehensive book on Epilepsy in Children. Key Features Epilepsy in Children is a common yet incompletely understood problem by general pediatricians. An exhaustive list of causes and multiple classifications add to the complexities of the issues. A plethora of new antiepileptic drugs has come in market and often we face difficulty in choosing appropriate molecule. Silver lining is that most of pediatric epilepsies are amenable to treatment with an excellent long-term outcome, provided the workup and management plan is executed methodically. Hence, this book, where Pediatric Neurologists from Indian Academy of Pediatrics (lAP) have given a knowhow of Pediatric Epilepsy in a simplified way. So, this book becomes an essential companion of pediatricians and residents
1. Classification of Epilepsy Satinder Aneja, Suvasnini Sharma Need for classification Types of classification Classification of seizures Classification of epilepsy and epileptic syndromes Common epileptic syndromes of infancy, childhood and adolescence Changes in the classification of epilepsy syndromes as per the 2010 classification 2. What is Not Seizure? How to Differentiate? Renu Suthar, Naveen Sankhyan Breath holding spells (BHS) Reflex anoxic seizures Syncope Sleep disorders Paroxysmal non-epileptic seizures (PNES) Stereotypies and self-stimulation 3. Investigations in Epilepsy: What and When? Rachana Dubey, Sheffali Gulati, Biswaroop Chakrabarty Clinical data Electroencephalography (EEG) or interictal EEG Neuroimaging Therapeutic drug monitoring and routine laboratory tests Genetic investigations 31 Metabolic testing in epilepsy Autoantibodies in epilepsy 4. Demystifying EEG: Simple Steps to Read EEG for Pediatricians Lokesh Lingappa, Ramesh Konanki Before requesting electroencephalogram Technical aspects of EEG recording Neonatal EEG Epileptiform abnormalities EEG in intensive care setting Activation procedures Step-by-step EEG reading 5. Febrile Seizures Sujata Kanher y otros 15 capítulos más
Incluye contenido
Incluye índice
Incluye bibliografía
Keywords: EPILEPSY -- CHILDREN; EPILEPSY -- CLASSIFICATION